2015
DOI: 10.1371/journal.pone.0129949
|View full text |Cite|
|
Sign up to set email alerts
|

The Distinct Role of the Amygdala, Superior Colliculus and Pulvinar in Processing of Central and Peripheral Snakes

Abstract: IntroductionVisual processing of ecologically relevant stimuli involves a central bias for stimuli demanding detailed processing (e.g., faces), whereas peripheral object processing is based on coarse identification. Fast detection of animal shapes holding a significant phylogenetic value, such as snakes, may benefit from peripheral vision. The amygdala together with the pulvinar and the superior colliculus are implicated in an ongoing debate regarding their role in automatic and deliberate spatial processing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 91 publications
(152 reference statements)
9
50
0
Order By: Relevance
“…A recent neurophysiological study reported that monkey SC neurons are highly sensitive to stimuli in the foveal VF than previously reported (Chen et al, 2019). Furthermore, fMRI studies reported a similar central bias for faces in the human SC as well as the amygdala in contrast with non-face objects (Almeida et al, 2013(Almeida et al, , 2015. The present results, as well as the previous imaging studies in the human SC and amygdala (Almeida et al, 2013(Almeida et al, , 2015, suggest that faces are also associated with central-biased representation in the subcortical visual system.…”
Section: Effects Of Rfs On Face Information Processingsupporting
confidence: 82%
“…A recent neurophysiological study reported that monkey SC neurons are highly sensitive to stimuli in the foveal VF than previously reported (Chen et al, 2019). Furthermore, fMRI studies reported a similar central bias for faces in the human SC as well as the amygdala in contrast with non-face objects (Almeida et al, 2013(Almeida et al, , 2015. The present results, as well as the previous imaging studies in the human SC and amygdala (Almeida et al, 2013(Almeida et al, , 2015, suggest that faces are also associated with central-biased representation in the subcortical visual system.…”
Section: Effects Of Rfs On Face Information Processingsupporting
confidence: 82%
“…Visual stimuli associated to danger in our evolutionary past, such as snakes and spiders, have also been studied during attentional and sensory unawareness. Non-conscious exposure to these stimuli evokes physiological arousal and amygdala response (Carlsson et al, 2004; Wendt et al, 2008; Alpers et al, 2009; Almeida et al, 2015), particularly if participants were phobic to these classes of stimuli, and activated Amg also when unattended because presented in the affected side of patients with hemispatial neglect (Tamietto et al, 2015). On the other hand, the alleged special status of faces in triggering non-conscious perception and Amg activity is at odd with negative evidence when non-emotional facial characteristics, such as gender or identity, are tested during unawareness (Rossion et al, 2000; Negro et al, 2015).…”
Section: Stimulus Categories and Properties Triggering Amygdala Respomentioning
confidence: 99%
“…This is supported by the latency of the emotion effects we observed at the sensor level (occurring at approximately 150ms). Some degree of pre-emptive processing in the pulvinar, however, is supported by previous research on pulvinar response-specificity to faces 24,56 and snakes 24,57,58 . There has been debate, though, over whether these pulvinar responses are generated independently or are a result of cortical mediation 6,8 .…”
Section: Discussionmentioning
confidence: 58%